2010
DOI: 10.2147/dddt.s8410
|View full text |Cite
|
Sign up to set email alerts
|

Sumatriptan-naproxen fixed combination for acute treatment of migraine: a critical appraisal

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs), including naproxen and naproxen sodium, are effective yet nonspecific analgesic and anti-inflammatory drugs, which work for a variety of pain and inflammatory syndromes, including migraine. In migraine, their analgesic effect helps relieve the headache, while their anti-inflammatory effect decreases the neurogenic inflammation in the trigeminal ganglion. This is the hypothesized mechanism by which they prevent the development of central sensitization. Triptans, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…Based on clinical observations on the temporal response to these drugs on migraine, sumatriptan/naproxen is proposed to function primarily at the level of the ganglia to abort a migraine attack. 37, 38 Our findings support such a notion. In this way, sumatriptan and naproxen repression of cytokines and signaling protein levels within the ganglia, as seen in our study, would suppress the development of peripheral sensitization of primary nociceptors, and hence limit the later development of central sensitization.…”
Section: Discussionsupporting
confidence: 86%
“…Based on clinical observations on the temporal response to these drugs on migraine, sumatriptan/naproxen is proposed to function primarily at the level of the ganglia to abort a migraine attack. 37, 38 Our findings support such a notion. In this way, sumatriptan and naproxen repression of cytokines and signaling protein levels within the ganglia, as seen in our study, would suppress the development of peripheral sensitization of primary nociceptors, and hence limit the later development of central sensitization.…”
Section: Discussionsupporting
confidence: 86%
“…[5] TTH may be treated with effective over-thecounter analgesic agents and the amelioration of any circumstances that may be triggering the headaches or causing the patient concern. [6,33] For instance, the efficacy of simple analgesics and NSAIDs is improved with the coadministration of caffeine, [4] with concomitant therapy with a NSAID and an antiemetic potentially providing relief from migraine-associated nausea and facilitating absorption. aspirin, paracetamol) or NSAIDs, the mainstays in episodic TTH therapy.…”
Section: Dosage and Administrationmentioning
confidence: 99%
“…Although triptans have been introduced as a safe and effective treatment for migraine attacks, this class of drugs has well‐known side effects and contraindications including chest pressure, neck tightness, limb heaviness, and tingling. Contraindications include vascular disease, coronary artery disease, and pregnancy . Several open‐label studies and case reports and one double‐blinded study have shown that subanesthetic doses of propofol are efficacious as rescue therapy for acute migraine headaches in adults and children .…”
Section: Introductionmentioning
confidence: 99%